Thin film adhesion strength evaluation method, thin film adhesion strength evaluation device, and test substrate
Patent Information
- Application Number
- JP2021090683
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-05-28
- Publication Date
- 2025-01-06
- Estimated Expiration
- 2041-05-28
AI Technical Summary
【0019】 密着強度の評価を適切に行える薄膜密着強度評価方法、薄膜密着強度評価装置及び試験用基板を提供することができる。
Smart Images

Figure 0007607923000001 
Figure 0007607923000002 
Figure 0007607923000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a thin film adhesion strength evaluation method, a thin film adhesion strength evaluation device, and a test substrate. [Background technology]
[0002] There is a need to appropriately evaluate the adhesive strength between a thin film and a substrate on which the thin film is formed. For example, in semiconductor devices, thin film materials at the submicron to nano level are used, and the thin film is formed (deposited) on a silicon or silicon dioxide substrate. Such a thin film may not be able to perform the desired function due to peeling from the substrate. Therefore, the adhesive strength between the thin film and the substrate is evaluated in relation to, for example, residual stress and impact forces such as friction and vibration.
[0003] Patent Document 1 describes an apparatus and method for measuring the tensile strength of ultrathin film interfaces and multilayers deposited on engineered substrates. The apparatus and method are said to use glass-modified stress waves to achieve separation and delamination of thin film lines or their complete structures from semiconductors and engineered substrates. The sample assembly evaluated by the apparatus and method is a multilayer with a fixed layer of solid water glass, an energy absorbing layer which is an aluminum layer, a glass substrate, a silicon substrate element and a coating with a free surface.
[0004] In the device and method described in Patent Document 1, a Nd-YAG laser pulse is applied to a sample assembly. The laser pulse travels in a direction that crosses the fixed layer. The laser pulse passes through the fixed layer and acts on the energy absorbing layer, which absorbs the energy, and heats it. The subsequent expansion of the energy absorbing layer generates a compressive shock wave or pulse wave. The compressive shock wave or pulse wave propagates through the glass substrate and the silicon substrate to the coating. The pulse wave or the like then penetrates the coating, reaches the free surface of the coating, and is reflected, generating a tensile pulse. This generates a tensile stress between the silicon substrate and the coating, causing the coating to peel off from the substrate. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2007-527538 A Summary of the Invention [Problem to be solved by the invention]
[0006] In the method described in Patent Document 1, a compressive stress wave propagated from the substrate (a silicon substrate in Patent Document 1) is reflected at the free end on the surface of a thin film (a coating film in Patent Document 1) to generate a tensile stress wave. Then, the tensile stress caused by the tensile stress wave is applied to the interface between the thin film and the substrate. However, in such a method, since the distance from the surface of the thin film to the interface with the substrate is short, the tensile stress acting at the interface is not large enough, and it may not be possible to apply a tensile stress strong enough to cause peeling to the interface. Therefore, it may not be possible to properly evaluate the adhesion strength. In addition, when a strong compressive stress wave is propagated from the substrate side to apply a tensile stress strong enough to cause peeling to the interface, the substrate may be damaged, and it may not be possible to properly evaluate the adhesion strength.
[0007] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a thin film adhesion strength evaluation method, a thin film adhesion strength evaluation device, and a test substrate that are capable of appropriately evaluating adhesion strength. [Means for solving the problem]
[0008] In order to achieve the above object, a method for evaluating thin film adhesion strength according to the present invention comprises the steps of: A method for evaluating adhesion strength between a thin film and a substrate, the method comprising the steps of: an energy absorption layer forming step of forming an energy absorption layer on the surface of the pressure propagation layer, the energy absorption layer receiving the laser light and generating a shock wave; an adhesive layer forming step of forming an adhesive layer on a surface of the pressure transmission layer opposite to the energy absorbing layer; a bonding step of bonding a surface of the thin film of the thin film forming substrate onto a surface of the adhesive layer opposite to the pressure propagation layer; an irradiation step of irradiating the energy absorbing layer with laser light; and a propagation step of propagating the shock wave generated in the irradiation step to the thin film formation substrate through the pressure propagation layer and the adhesive layer, In the propagation step, the shock wave is reflected by a surface of the substrate opposite to the thin film to generate an expansion wave, and the expansion wave is made to act on the thin film.
[0009] The thin film adhesion strength evaluation method according to the present invention further includes: An aluminum substrate made of aluminum or an aluminum alloy may be used as the pressure propagation layer.
[0010] The thin film adhesion strength evaluation method according to the present invention further includes: The energy absorbing layer may be formed from a viscous fluid containing graphite.
[0011] The viscous fluid may be replaced in sequence.
[0012] The thin film adhesion strength evaluation method according to the present invention further includes: A transparent substrate may be used as the substrate, and the interface between the thin film and the substrate may be optically observed through the surface of the substrate opposite to the thin film.
[0013] In order to achieve the above object, the thin film adhesion strength evaluation device according to the present invention comprises: A laser light source that emits laser light; and A test substrate is provided on which a thin film-formed substrate having a thin film formed thereon is mounted, The test substrate comprises: an energy absorbing layer that receives the laser light and generates a shock wave; A pressure transmission layer disposed on one side of the energy absorbing layer; and an adhesive layer disposed on a surface of the pressure transmission layer opposite the energy absorbing layer; The surface of the thin film on the thin film substrate is adhered to the surface of the adhesive layer opposite to the pressure propagation layer, thereby mounting the thin film substrate.
[0014] The thin film adhesion strength evaluation device according to the present invention further comprises: The pressure transmission layer may include an aluminum substrate made of aluminum or an aluminum alloy.
[0015] The thin film adhesion strength evaluation device according to the present invention further comprises: The energy absorbing layer may be formed of a viscous fluid containing graphite.
[0016] The thin film adhesion strength evaluation device according to the present invention further comprises: The system may further include a pump for sequentially replacing the viscous fluid.
[0017] The thin film adhesion strength evaluation device according to the present invention further comprises: The optical fiber may further include an imaging device that images an interface between the thin film and the substrate via a surface of the substrate opposite to the thin film.
[0018] In order to achieve the above object, the test substrate according to the present invention comprises: An energy absorbing layer that receives laser light and generates shock waves; A pressure transmission layer disposed on one side of the energy absorbing layer; and an adhesive layer disposed on a surface of the pressure transmission layer opposite the energy absorbing layer; The pressure transmission layer includes an aluminum substrate made of aluminum or an aluminum alloy, The energy absorbing layer is formed of a viscous fluid containing graphite. Effect of the Invention
[0019] It is possible to provide a thin film adhesion strength evaluation method, a thin film adhesion strength evaluation device, and a test substrate that can appropriately evaluate adhesion strength. [Brief description of the drawings]
[0020] [Figure 1] FIG. 1 is a diagram illustrating the overall configuration of a thin film adhesion strength evaluation device. [Diagram 2] FIG. 2 is a diagram illustrating the structure of a test piece. [Diagram 3] 1A to 1C are diagrams illustrating the change in state from the generation of a shock wave to the separation of an interface. [Figure 4] 1A and 1B are diagrams illustrating a configuration of a thin film forming substrate. [Diagram 5] FIG. 2 is a diagram illustrating a configuration of a test substrate. [Figure 6] 1 is a graph showing the magnitude of tensile stress in comparison with the prior art. [Figure 7] FIG. 2 is a diagram showing the results of evaluation of thin film adhesion strength in Example 1. [Figure 8] FIG. 13 is a diagram showing the results of evaluation of thin film adhesion strength in Example 2. [Figure 9] FIG. 1 shows a broken state of a silicon dioxide substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS A thin film adhesion strength evaluation method, a thin film adhesion strength evaluation device, and a test substrate according to an embodiment of the present invention will be described with reference to the drawings.
[0022] (Overall configuration) 1 shows a thin film adhesion strength evaluation apparatus 100 (hereinafter, referred to as the evaluation apparatus 100) according to this embodiment. The evaluation apparatus 100 is an apparatus for evaluating the adhesion strength between a thin film 11 and a substrate 10 in a thin film-formed substrate 1 in which a thin film 11 is formed on a substrate 10, that is, for implementing a thin film adhesion strength evaluation method.
[0023] The evaluation device 100 includes a laser light source 91 that irradiates laser light L, and a test substrate 2 on which a thin film formed substrate 1 is mounted.
[0024] 1 shows, as an example, a case where the evaluation device 100 further includes a container C for holding the thin film formed substrate 1 and the test substrate 2, and an imaging device 92. Also, as an example, a case where the laser light source 91 includes a lens 91a for focusing the laser light L is shown.
[0025] 2, the test substrate 2 has an energy absorbing layer 22 that receives laser light L and generates a shock wave, a pressure propagation layer 23 arranged on one side of the energy absorbing layer 22, and an adhesive layer 24 arranged on the surface of the pressure propagation layer 23 opposite the energy absorbing layer 22. The test substrate 2 has the surface of the thin film 11 of the thin-film-formed substrate 1 bonded to the surface of the adhesive layer 24 opposite the pressure propagation layer 23. By bonding the thin film 11 to the adhesive layer 24 in this manner, the thin film-formed substrate 1 is attached to the test substrate 2.
[0026] The thin film adhesion strength evaluation method for evaluating the adhesion strength between the thin film 11 and the substrate 10 in the thin film-formed substrate 1 in this embodiment includes an absorption layer formation step of forming an energy absorption layer 22 on the surface of the pressure propagation layer 23, an adhesive layer formation step of forming an adhesive layer 24 on the surface of the pressure propagation layer 23 opposite the energy absorption layer 22, a bonding step of bonding the surface of the thin film 11 in the thin film-formed substrate 1 to the surface of the adhesive layer 24 opposite the pressure propagation layer 23, an irradiation step of irradiating the energy absorption layer 22 with laser light L, and a propagation step of propagating the shock wave generated in the irradiation step to the thin film-formed substrate 1 via the pressure propagation layer 23 and the adhesive layer 24.
[0027] 3 shows the change in state (states (a) to (d)) from the generation of the shock wave to the peeling of the interface during the irradiation process to the propagation process. In the propagation process, as shown in FIG. 3(c), the shock wave W is reflected by the free end on the surface of the substrate 10 opposite the thin film 11 to generate an expansion wave W2, which is then applied to the thin film 11.
[0028] 1, the evaluation device 100 irradiates a test substrate 2 on which a thin film-formed substrate 1 is mounted with laser light L from a laser light source 91, and applies a shock wave W (expansion wave W2, see FIG. 3) to the interface between a thin film 11 in the thin film-formed substrate 1 and the substrate 10, thereby observing a change in the interface between the thin film 11 and the substrate 10, i.e., evaluating the thin film adhesion strength. The observation of the change in the interface between the thin film 11 and the substrate 10 is performed using, for example, an imaging device 92.
[0029] (Explanation of each part) 4 shows a schematic structure of the thin film-formed substrate 1. The thin film-formed substrate 1 is a sample to be evaluated in the thin film adhesion strength evaluation. The thin film-formed substrate 1 includes a substrate 10 and a thin film 11 formed on the substrate 10. The thin film-formed substrate 1 is, for example, a semiconductor device or a precursor thereof.
[0030] The substrate 10 is a plate-shaped base material for forming the thin film 11. An example of the substrate 10 is a plate-shaped base material such as silicon or silicon dioxide, for example, a wafer for manufacturing semiconductor devices. The substrate 10 is preferably optically transparent. The thickness of the substrate 10 is, for example, 100 μm or more and 3 mm or less. In this embodiment, as an example, the thickness of the substrate 10 can be 0.5 mm. In this embodiment, a case will be described in which the substrate 10 is a substrate made of silicon dioxide that is transparent to visible light.
[0031] The thin film 11 is a thin film or a thin layer formed by epitaxial growth, for example, by a CVD method or a sputtering method. In this embodiment, the method of forming the thin film 11 is not limited. The thin film 11 is, for example, a metal or semiconductor film or layer. The thickness of the thin film 11 is, for example, 10 nm or more and 500 nm or less. In this embodiment, the thickness of the thin film 11 can be, for example, 200 nm. Hereinafter, the concept of film and layer is collectively referred to simply as thin film.
[0032] As shown in FIG. 1, the evaluation device 100 includes a laser light source 91, a test substrate 2 on which a thin film-formed substrate 1 is mounted, a holding container C that fixes and holds the test substrate 2 (test piece T described later) on which the thin film-formed substrate 1 is mounted, and an imaging device 92 that optically observes the test piece T.
[0033] Fig. 5 shows a schematic structure of the test substrate 2. The test substrate 2 is an auxiliary substrate for evaluating the thin film adhesion strength of the thin film-formed substrate 1. As shown in Fig. 2, the thin film-formed substrate 1 is attached to the test substrate 2 by adhesion or the like. The test substrate 2 with the thin film-formed substrate 1 attached thereto may be hereinafter referred to as a test piece T.
[0034] 5, the test substrate 2 has the energy absorbing layer 22, the pressure transmission layer 23, and the adhesive layer 24 as described above. In this embodiment, the test substrate 2 further has a fixing layer 21 arranged on the surface of the energy absorbing layer 22 opposite to the pressure transmission layer 23. That is, the test substrate 2 has a structure in which the fixing layer 21, the energy absorbing layer 22, the pressure transmission layer 23, and the adhesive layer 24 are laminated in this order. The fixing layer 21, the energy absorbing layer 22, the pressure transmission layer 23, and the adhesive layer 24 are each in close contact with the adjacent layers.
[0035] The pressure propagation layer 23 is a layer for propagating the shock wave generated in the energy absorbing layer 22 toward the thin film substrate 1. For the pressure propagation layer 23, it is preferable to select a material that is unlikely to attenuate the shock wave and has an acoustic impedance value close to that of the energy absorbing layer 22 and the adhesive layer 24. It is also preferable to select a material that is ductile and unlikely to be damaged by the propagation of the shock wave. It is also preferable to use a material with high thermal conductivity. An example of a preferable material is a metal material, particularly aluminum or an aluminum alloy. That is, the pressure propagation layer 23 may include an aluminum substrate formed of aluminum or an aluminum alloy. In this embodiment, a case where the pressure propagation layer 23 is formed of an aluminum substrate formed of an aluminum alloy (A2017) is described as an example.
[0036] The pressure transmission layer 23 is preferably formed to a thickness of about 1 mm to 9 mm. In the present embodiment, as an example, the pressure transmission layer 23 may have a thickness of 3 mm. If the pressure transmission layer 23 is thinner than 1 mm, the shock waves generated in the energy absorbing layer 22 may not be properly transmitted to the thin film substrate 1. Furthermore, the pressure transmission layer 23 may be deformed. If the pressure transmission layer 23 is thicker than 10 mm, the shock waves may be attenuated by the pressure transmission layer 23, and shock waves of appropriate strength may not be properly transmitted to the thin film substrate 1.
[0037] The energy absorbing layer 22 is a layer that receives the laser light L and generates shock waves. The energy absorbing layer 22 is formed by coating or the like on the surface of the pressure propagation layer 23. As an example, the energy absorbing layer 22 converts the energy supplied by the laser light L into heat, and the heat causes the energy absorbing layer 22 to rapidly evaporate itself and rapidly expand, thereby generating shock waves.
[0038] The energy absorbing layer 22 of this embodiment is formed of a viscous fluid containing graphite and an oil component (grease). The energy absorbing layer 22 contains graphite, so that the laser light L can be efficiently converted into thermal energy. The energy absorbing layer 22 contains an oil component, so that the energy absorbing layer 22 can be a flowable viscous fluid.
[0039] In this embodiment, the energy absorbing layer 22 is formed of a viscous fluid that circulates inside and outside the test substrate 2. FIG. 1 shows a case where the evaluation device 100 includes a tank 93 that stores the viscous fluid, and a pump 94 that circulates the viscous fluid inside and outside the test substrate 2. The pump 94 supplies the viscous fluid to the test substrate 2 through a supply path F1, and sequentially replaces the viscous fluid as the energy absorbing layer 22 (see FIG. 2). The replaced viscous fluid is discharged from the test substrate 2 through a discharge path F2. In this manner, the viscous fluid of the energy absorbing layer 22 may be circulated in the test substrate 2.
[0040] The energy absorbing layer 22 shown in FIG. 5 is preferably formed to a thickness of 50 μm or more and 200 μm or less. If the energy absorbing layer 22 is thinner than 50 μm, it may not be possible to generate shock waves of sufficient strength. In particular, when circulating a viscous fluid inside and outside the test substrate 2 using the pump 94 (see FIG. 1), if the energy absorbing layer 22 is thinner than 50 μm, the pressure when circulating the viscous fluid increases, and the power of the pump 94 may be insufficient to ensure proper circulation of the viscous fluid. If the energy absorbing layer 22 is thicker than 200 μm, the energy absorbing layer 22 may absorb the shock waves, and shock waves of sufficient strength may not be propagated to the pressure propagation layer 23.
[0041] Since the energy absorbing layer 22 is a viscous fluid, the energy absorbing layer 22 can repeatedly generate shock waves even when the laser light L is repeatedly received. That is, when the energy absorbing layer 22 receives the laser light L, a part of the layer 22 evaporates, and a hole-like or void-like light receiving mark is formed. However, since the energy absorbing layer 22 is a fluid, the layer 22 can self-regenerate (hereinafter simply referred to as self-regeneration) to fill in the light receiving mark. This enables the energy absorbing layer 22 to repeatedly generate shock waves. This self-regeneration is performed efficiently (in a short time and reliably) especially when a viscous fluid is circulated inside and outside the test substrate 2 by a pump 94 (see FIG. 1).
[0042] The fixing layer 21 is a solid layer such as glass that can transmit the laser light L. The fixing layer 21 is disposed on the surface of the energy absorbing layer 22 opposite to the pressure propagation layer 23. In this embodiment, a case where a plate-shaped sapphire glass is used as the fixing layer 21 will be described as an example. The energy absorbing layer 22 is sandwiched between the fixing layer 21 and the pressure propagation layer 23, and the energy absorbing layer 22 is held between the fixing layer 21 and the pressure propagation layer 23. The thickness of the fixing layer 21 is preferably 3 mm or more and 10 mm or less. The thickness of the fixing layer 21 is preferably 4 mm or more and 6 mm or less. For example, the thickness of the fixing layer 21 may be 5 mm. If the fixing layer 21 is thinner than 3 mm, the fixing layer 21 may become fragile and may become difficult to handle. If the thickness of the fixed layer 21 becomes too thick, the laser light L emitted by the laser light source 91 and focused by the lens 91a (see FIG. 1) may be distorted (for example, the focused laser light L may be diffused). If the laser light L is distorted, there is a possibility that energy may not be appropriately supplied to the fixed layer 21.
[0043] The adhesive layer 24 is a layer for adhering the thin film substrate 1 to the test substrate 2. The adhesive layer 24 is disposed on the surface of the pressure transmission layer 23 opposite to the energy absorption layer 22. The adhesive layer 24 is made of a material that has an acoustic impedance close to those of the pressure transmission layer 23 and the thin film substrate 1 and has a function of adhering the thin film substrate 1. In this embodiment, a case in which the adhesive layer 24 is made of epoxy resin will be described as an example.
[0044] The adhesive layer 24 is formed on the surface of the pressure transmission layer 23 by coating or the like. The adhesive layer 24 may be formed on the surface of the pressure transmission layer 23 immediately before bonding the thin-film-formed substrate 1 to the test substrate 2. The thin-film-formed substrate 1 is attached to the test substrate 2 by bonding the surface of the thin film 11 of the thin-film-formed substrate 1 to the surface of the adhesive layer 24.
[0045] As shown in FIG. 1, the holding container C is a holder that fixes and holds the thin test piece T. In FIG. 1, the holding container C and the test piece T held therein are shown in a schematic perspective view, and the central portion is shown as a vertical cross-sectional view. As an example, the holding container C may hold the test piece T by surrounding the outer periphery of the test piece T. It is preferable that the holding container C is capable of holding the test piece T by sandwiching it in the thickness direction. The holding container C opens both sides of the central portion of the test piece T to the outside. This allows the test piece T to receive the laser light L irradiated from the laser light source 91. In addition, the test piece T can be observed by the imaging device 92.
[0046] As described above, the laser light source 91 is a light source that irradiates the test piece T with laser light L. The laser light source 91 may be any light source that can irradiate laser light L of a predetermined intensity for a predetermined period of time. In this embodiment, the laser light source 91 is an Nd-Yag laser light source, and is described as an example of a light source that can irradiate laser pulses as laser light L of a predetermined intensity and for a predetermined period of time. The laser light source 91 is preferably capable of outputting laser light L with a pulse energy of 50 mJ or more, and a pulse width that can be adjusted within a range of 5 nm or more and 7 nm or less.
[0047] The laser light source 91 irradiates the laser light L toward the test substrate 2 side (fixing layer 21) of the test piece T. The laser light L may be irradiated to the test piece T, for example, perpendicularly or obliquely.
[0048] The imaging device 92 is a device that images the test piece T to realize optical observation. A so-called camera may be used as the imaging device 92. The imaging device 92 may include a microscope or a magnifying lens system corresponding to a microscope as an optical system. The imaging device 92 images the thin film-formed substrate 1 (substrate 10) side of the test piece T. In this embodiment, since the substrate 10 is a transparent substrate, the imaging device 92 images the interface between the thin film 11 and the substrate 10 through the surface of the substrate 10 opposite to the thin film 11, thereby making it possible to optically observe the interface between the thin film 11 and the substrate 10.
[0049] The thin film adhesion strength evaluation using the evaluation apparatus 100 will be described with reference to FIGS.
[0050] As shown in FIG. 1, the test piece T is mounted in a holding container C. Then, as shown in FIG. 3, a laser light L is irradiated from a laser light source 91 toward the energy absorbing layer 22 (see FIG. 3(a)). The irradiation of the laser light L causes a part of the energy absorbing layer 22 to rapidly evaporate, generating bubbles B (so-called laser ablation). When the bubbles B are generated, a compression wave W1 is generated as a shock wave W (see FIG. 3(b)). The compression wave W1 propagates to the thin film substrate 1 via the pressure propagation layer 23 and the adhesive layer 24. That is, the energy of the laser light L is converted into the energy of the shock wave W through the generation of the bubbles B.
[0051] During the propagation of the compression wave W1, the pressure propagation layer 23 is formed of a ductile material such as an aluminum substrate, and therefore the pressure propagation layer 23 is free from damage (is prevented from being damaged) during the propagation of the compression wave W1. In addition, the pressure propagation layer 23 is made of a material that is less susceptible to shock wave attenuation and has an acoustic impedance value close to that of the energy absorbing layer 22 and the adhesive layer 24, and therefore attenuation of the compression wave W1 (loss of energy of the shock wave W) can be suppressed. In addition, since the pressure propagation layer 23 has a high thermal conductivity, cooling of the energy absorbing layer 22 and the pressure propagation layer 23 proceeds quickly, and repeated irradiation of the laser light L from the laser light source 91 (repeated generation of shock waves W) is possible.
[0052] When the compression wave W1 reaches the substrate 10 and further reaches the surface of the substrate 10 opposite the thin film 11, the compression wave W1 is reflected at the free end on the surface of the substrate 10. This reflection causes the compression wave W1 to become an expansion wave W2 as a shock wave W, and propagates from the substrate 10 toward the thin film 11 (see FIG. 3(c)). Note that the substrate 10 is not in direct contact with the energy absorbing layer 22, and the compression wave W1 is propagated via the pressure propagation layer 23 and the adhesive layer 24, so that the substrate 10 does not receive large amounts of energy locally. Therefore, damage to the substrate 10 caused by the compression wave W1 is suppressed.
[0053] When the expansion wave W2 propagates from the substrate 10 toward the thin film 11 and reaches the interface between the substrate 10 and the thin film 11, the energy of the expansion wave W2 generates a tensile stress at the interface between the substrate 10 and the thin film 11 as a force for peeling the interface. Since the interface between the substrate 10 and the thin film 11 is a sufficient distance away from the surface of the substrate 10 where the expansion wave W2 is reflected, the tensile stress is sufficiently excited when the expansion wave W2 reaches the interface between the substrate 10 and the thin film 11. Therefore, in the thin film adhesion strength evaluation method according to this embodiment, it is not necessary to make the energy of the shock wave W (the energy of the laser light L) excessively large.
[0054] FIG. 6 shows a graph of the difference in magnitude between the tensile stress when the interface between the substrate 10 and the thin film 11 is sufficiently distant from the surface of the substrate 10 where the expansion wave W2 is reflected, as in this embodiment ("this embodiment" in the figure), and the tensile stress when the interface between the substrate and the thin film is not sufficiently distant from the surface where the shock wave is reflected, as in the conventional technology described in Patent Document 1 (corresponding to the case where the distance from the surface of the thin film to the interface with the substrate is short in Patent Document 1, the conventional technology in the figure). In FIG. 6, the tensile stress acting on these interfaces is shown on the vertical axis as the interface load stress, and the time elapsed from the time point when the laser light L is irradiated as time 0 (zero) is shown on the horizontal axis. In this embodiment, after a predetermined time has elapsed after irradiation of the laser light L, an interface load stress with a large amplitude that goes from the negative side to the positive side is detected. In contrast, in the conventional technology, only a very small amplitude is detected. In this way, in this embodiment, a large tensile stress (interface load stress in FIG. 6) that is incomparable to the conventional technology can be applied to the interface.
[0055] If the adhesion strength at the interface between the substrate 10 and the thin film 11 is such that peeling occurs due to the energy of the expansion wave W2, the interface peels off, and a peeling mark P is formed (see FIG. 3(d)). The peeling mark P can be optically observed by the imaging device 92. If the adhesion strength at the interface between the substrate 10 and the thin film 11 is such that peeling does not occur due to the energy of the expansion wave W2, no change occurs at the interface.
[0056] In this way, the evaluation device 100 realizes an evaluation of whether or not the adhesion strength of the interface between the substrate 10 and the thin film 11 is strong enough to cause peeling due to the energy of the expansion wave W2. In this adhesion strength evaluation, damage to the pressure propagation layer 23 and the substrate 10 is prevented or suppressed, so that the adhesion strength can be appropriately evaluated.
[0057] The energy of the expansion wave W2 correlates with the energy of the shock wave W. That is, the energy of the expansion wave W2 correlates with the energy of the laser light L. Therefore, in the evaluation device 100, the total amount of energy of the laser light L (for example, the pulse length of the laser light L) or the amount of energy per unit time (for example, the intensity of the laser light L) is changed, thereby changing the amount of energy applied to the interface between the substrate 10 and the thin film 11, and the adhesion strength can be evaluated. That is, if the evaluation is performed by changing the energy of the expansion wave W2 by changing the energy of the laser light L, it is possible to realize an evaluation of the adhesion strength at the interface between the substrate 10 and the thin film 11, that is, the strength of the adhesion strength. In this way, the evaluation device 100 can also realize an evaluation of the adhesion strength at the interface between the substrate 10 and the thin film 11.
[0058] In evaluating the adhesion strength, it is preferable to use the imaging device 92, since the peeling state of the interface between the substrate 10 and the thin film 11 can be optically grasped, for example, as an image. For example, the adhesion strength can be evaluated based on the area of the peeled portion of the interface between the substrate 10 and the thin film 11, or the adhesion state or characteristics at the time of peeling can be evaluated as an example of adhesion strength, based on the shape of the peeled portion of the interface with the thin film 11.
[0059] (Example) An embodiment of the adhesion evaluation using the evaluation device 100 will be described with reference to FIGS.
[0060] Example 1 FIG. 7 shows the results of evaluating the thin film adhesion strength of a thin film-formed substrate in which a copper film was formed by vapor deposition on a silicon dioxide substrate. FIG. 7(a) is an image of the interface state of the thin film-formed substrate before peeling, taken from the silicon dioxide substrate side. FIG. 7(b) is an image of the peeled interface state (after irradiation with a pulse of laser light L) that occurred when a pulse of laser light L of 260 mJ was irradiated, with the energy of the initial pulse of laser light L set to 200 mJ, and multiple irradiations were repeated while increasing the energy of the pulse of laser light L by 10 mJ from 200 mJ until peeling occurred at the interface. That is, FIG. 7(a) shows the interface state from before irradiation with laser light L to the point at which a pulse of laser light L of 250 mJ was irradiated.
[0061] In the image of FIG. 7(a), the shading is uniform throughout the image. In contrast, in the image of FIG. 7(b), the peeling marks can be seen as areas in the center of the image that are lighter in color than the peripheral areas. In other words, it is clear that peeling has occurred at the interface in the center of the image. This allows the thin film substrate of Example 1 to be evaluated as having an adhesion strength that is sufficient to cause peeling at the interface when an energy of more than 250 mJ, at least 260 mJ, is supplied.
[0062] Example 2 FIG. 8 shows the thin film adhesion strength evaluation results of a thin film-formed substrate in which a copper film and a titanium film are formed on a silicon dioxide substrate by vapor deposition. FIG. 8(a) is an image of the interface state of the thin film-formed substrate before peeling, taken from the silicon dioxide substrate side. FIG. 8(b) is an image of the interface peeling state (after irradiation of laser light L) that occurs when irradiating a pulse of 360 mJ of laser light L by repeatedly irradiating the interface until peeling occurs while increasing the energy of the pulse of laser light L by 10 mJ from 200 mJ in the same manner as in Example 1. That is, FIG. 8(a) shows the interface state from before irradiation of laser light L to the point of irradiation of a pulse of 350 mJ of laser light L.
[0063] In the image of Fig. 8(a), the shading is uniform throughout the image. In contrast, in the central part of the image of Fig. 8(b), mottled peeling marks can be observed. This indicates that the thin film substrate of Example 2 has an adhesion strength that causes peeling at the interface when an energy of at least 360 mJ is applied, exceeding 350 mJ.
[0064] In addition, when only a silicon dioxide substrate was attached to the test substrate 2 and irradiated with laser light L in the same manner as in Examples 1 and 2, no damage occurred to the silicon dioxide substrate until it was irradiated with a pulse of 400 mJ of laser light L. FIG. 9 shows an image (see FIG. 9(a)) of the state of the silicon dioxide substrate until it was irradiated with a pulse of 390 mJ of laser light L, and an image (see FIG. 9(b)) of the state of the silicon dioxide substrate damaged as a result of being irradiated with a pulse of 400 mJ of laser light L. Considering that no damage occurred to the silicon dioxide substrate until it was irradiated with a pulse of 400 mJ of laser light L, it is clear that the peeling marks described in Examples 1 and 2 are not damage to the silicon dioxide substrate.
[0065] In this manner, a thin film adhesion strength evaluation method and a thin film adhesion strength evaluation device for implementing the method can be provided.
[0066] [Another embodiment] (1) In the above embodiment, the thin film adhesion strength evaluation results were described in the examples, in which the energy of the pulse of laser light L was increased little by little (by 10 mJ), multiple irradiations were repeated until peeling occurred at the interface, and the peeling state at the interface when peeling occurred was imaged. However, the thin film adhesion strength evaluation is not limited to this mode. For example, a fatigue test in which pulses of laser light L with the same energy are repeatedly irradiated and the number of irradiations until peeling occurs can be compared as the thin film adhesion strength evaluation. In addition, when evaluating the thin film adhesion strength, it is also possible to irradiate a pulse of laser light L with a predetermined energy only once without repeatedly irradiating the pulse of laser light L, and evaluate whether peeling occurs or not.
[0067] (2) In the above embodiment, the peeling trace P is optically observed by the imaging device 92. However, the imaging device 92 is not essential. For example, the test piece T may be removed from the holding container C each time the laser light L is irradiated, and observed under a microscope. In addition, the observation of the peeling trace P is not limited to optical observation (including visual observation), and ultrasonic echo or X-ray transmission observation is not excluded.
[0068] (3) In the above embodiment, the substrate 10 is optically transparent. However, it is not essential that the substrate 10 is transparent. Even if the substrate 10 is opaque, the interface may be observed from the thin film 11 side by peeling the thin film-formed substrate 1 from the test piece T, and the interface and the peeling trace P may be observed by transmission observation using ultrasonic echo or X-ray.
[0069] (4) In the above embodiment, the pressure propagation layer 23 includes an aluminum substrate. However, the pressure propagation layer 23 is not limited to an aluminum substrate. The pressure propagation layer 23 may be silicon or silicon dioxide. Even in this case, the interface between the substrate 10 and the thin film 11 is still a sufficient distance away from the surface of the substrate 10 where the expansion wave W2 is reflected. Even if the energy of the shock wave W propagating to the pressure propagation layer 23 is not increased, when the expansion wave W2 reaches the interface between the substrate 10 and the thin film 11, a sufficient tensile stress can be excited at the interface. This makes it possible to suppress damage to the pressure propagation layer 23, which is a problem in the prior art.
[0070] (5) In the above embodiment, the energy absorbing layer 22 is formed of a viscous fluid. However, it is not essential that the energy absorbing layer 22 is formed of a viscous fluid. The energy absorbing layer 22 may be a solid layer, for example, a thin aluminum layer.
[0071] (6) In the above embodiment, it has been described that the pump 94 supplies the viscous fluid to the test substrate 2 via the supply path F1, sequentially replacing the viscous fluid as the energy absorbing layer 22, and that the replaced viscous fluid is discharged from the test substrate 2 via the discharge path F2. However, the replacement of the viscous fluid in the pump 94 or the energy absorbing layer 22 of the test substrate 2 is not essential. Self-regeneration functions even if the viscous fluid in the pump 94 or the energy absorbing layer 22 is not replaced.
[0072] In addition, the configurations disclosed in the above embodiments (including other embodiments, the same applies below) can be applied in combination with configurations disclosed in other embodiments, provided no contradiction arises. Furthermore, the embodiments disclosed in this specification are illustrative, and the embodiments of the present invention are not limited thereto, and can be appropriately modified within the scope that does not deviate from the purpose of the present invention. [Industrial Applicability]
[0073] The present invention can be applied to a thin film adhesion strength evaluation method, a thin film adhesion strength evaluation device, and a test substrate. [Explanation of symbols]
[0074] 1 Thin film formation substrate 2 Test board 10 Substrate 11 Thin Films 21 Fixed layer 22 Energy absorbing layer 23 Pressure Transmission Layer 24 Adhesive layer 91 Laser Light Source 91a Lens 92 Imaging Device 93 Tank 94 Pump 100 Evaluation equipment (thin film adhesion strength evaluation equipment) B. Air bubbles C Holding container L Laser light P Peeling marks T test piece W Shock Wave W1 compression wave W2 Expansion wave
Claims
1. A method for evaluating adhesion strength between a thin film and a substrate, the method comprising the steps of: an energy absorption layer forming step of forming an energy absorption layer on the surface of the pressure propagation layer, the energy absorption layer receiving the laser light and generating a shock wave; an adhesive layer forming step of forming an adhesive layer on a surface of the pressure transmission layer opposite to the energy absorbing layer; a bonding step of bonding a surface of the thin film of the thin film forming substrate onto a surface of the adhesive layer opposite to the pressure propagation layer; an irradiation step of irradiating the energy absorbing layer with laser light; and a propagation step of propagating the shock wave generated in the irradiation step to the thin film formation substrate through the pressure propagation layer and the adhesive layer, In the propagation step, the shock wave is reflected from a surface of the substrate opposite the thin film to generate an expansion wave, and the expansion wave is caused to act on the thin film.
2. 2. The method for evaluating adhesion strength of a thin film according to claim 1, wherein an aluminum substrate made of aluminum or an aluminum alloy is used as the pressure propagation layer.
3. The method for evaluating adhesion strength of a thin film according to claim 1 or 2, wherein the energy absorbing layer is formed of a viscous fluid containing graphite.
4. The method for evaluating adhesion strength of a thin film according to claim 3 , wherein the viscous fluid is replaced successively.
5. 5. The method for evaluating thin film adhesion strength according to claim 1, wherein a transparent substrate is used as the substrate, and the interface between the thin film and the substrate is optically observed through a surface of the substrate opposite to the thin film.
6. A laser light source that emits laser light; and A test substrate is provided on which a thin film-formed substrate having a thin film formed thereon is mounted, The test substrate comprises: an energy absorbing layer that receives the laser light and generates a shock wave; A pressure transmission layer disposed on one side of the energy absorbing layer; and an adhesive layer disposed on a surface of the pressure transmission layer opposite the energy absorbing layer; A thin film adhesion strength evaluation device in which the thin film substrate is attached by adhering the surface of the thin film on the thin film substrate to the surface of the adhesive layer opposite to the pressure propagation layer.
7. The thin film adhesion strength evaluation device according to claim 6 , wherein the pressure propagation layer includes an aluminum substrate made of aluminum or an aluminum alloy.
8. 8. The thin film adhesion strength evaluation device according to claim 6, wherein the energy absorbing layer is formed of a viscous fluid containing graphite.
9. The thin film adhesion strength evaluation device according to claim 8 , further comprising a pump for successively replacing the viscous fluid.
10. The thin film adhesion strength evaluation apparatus according to claim 6 , further comprising an imaging device that images an interface between the thin film and the substrate via a surface of the substrate opposite to the thin film.
11. An energy absorbing layer that receives laser light and generates shock waves; A pressure transmission layer disposed on one side of the energy absorbing layer; and an adhesive layer disposed on a surface of the pressure transmission layer opposite the energy absorbing layer; The pressure transmission layer includes an aluminum substrate made of aluminum or an aluminum alloy, The energy absorbing layer is a test substrate formed of a viscous fluid containing graphite.
Citation Information
Patent Citations
Measuring device
JP2005300273A
Glass modification stress wave and nanoelectronic device fabrication for separating ultrathin films
JP2007527538A
Cited By
Thin film adhesion strength evaluation method and thin film adhesion strength evaluation device
JP2024067973A